Offshore Risk Assessment Principles, Modelling and Applications of QRA Studies - Vinnem, Jan-Erik (Springer Series in Reliability Engineering,, 2007)
Offshore Risk Assessment was the first book to deal with quantified risk assessment (QRA) as applied specifically to offshore installations and operations. Risk assessment techniques have been used for more than three decades in the offshore oil and gas industry, and their use is set to expand increasingly as the industry moves into new areas and faces new challenges in older regions. This updated and expanded second edition has been informed by a major R&D programme on offshore risk assessment in Norway (2002-2006), and reflects the trend of expanded use of floating production installations. It starts with a thorough discussion of risk metrics and risk analysis methodology with subsequent chapters devoted to analytical approaches to escalation, escape, evacuation and rescue analysis of safety and emergency systems. Separate chapters analyse the main hazards of offshore structures: fire, explosion, collision and falling objects. Risk mitigation and control are discussed, as well as an illustration of how the results from quantitative risk assessment studies should be presented. The second edition has a stronger focus on the use of risk assessment techniques in the operation of offshore installations. Also decommissioning of installations is covered. Not only does Offshore Risk Assessment describe the state of the art of QRA, it also identifies weaknesses and areas that need further development. A comprehensive reference for academics and students of marine/offshore risk assessment and management, the book should also be owned by professionals in the industry, contractors, suppliers, consultants and regulatory authorities. Dr Jan Erik Vinnem is Professor of Risk Analysis and Management at the University of Stavanger. He is a Specialist Advisor and CEO of Preventor AS, a small consultancy to the Norwegian offshore industry. His professional career includes several years in the petroleum industry (Statoil, Total), over 20 years in consultancy and some years, now expanding, in research and education. Springer Series in Reliability Engineering publishes high-quality books in important areas of current theoretical research and development in reliability, and in areas that bridge the gap between theory and application in areas of interest to practitioners in industry, laboratories, business, and government.